Legal Protection for Medical Personnel in BPJS Affiliated Hospitals Based on Law Number 17 of 2023 - Gladys Haryanto; Erna Ambarwati; Lany, Arman (LifeSciFi, 2025)
Technological developments and the need for better healthcare services are driving the transformation of health law in Indonesia. This study aims to analyze the impact of Law Number 17 of 2023 concerning Health on legal protection for healthcare workers and patients. The study used a qualitative approach using literature study methods and legal document analysis. Data were collected from laws and regulations, scientific journals, and official health-related documents. The findings indicate that the law strengthens legal protection for healthcare workers by clarifying their rights and obligations, including in anesthesia services and emergency treatment. For patients, the law improves access to equitable healthcare services and ensures the confidentiality of medical records. However, implementation still faces challenges, such as a lack of public awareness and harmonization with previous regulations. This study concludes that Law No. 17 of 2023 provides a strong foundation for a more structured healthcare system, but its success depends on consistent implementation and inter-agency coordination. This study recommends increased training for healthcare workers and public outreach to support the effective implementation of this law.